Polyvictimization across social contexts: home, school, and neighborhood violence exposure - Butcher, Fredrick (Criminal justice and behavior, 2016)
Exposure to violence is a widespread problem that affects the mental health of children and adolescents particularly in at-risk populations such as juvenile justice involved youth. While a number of studies have examined the cumulative impact of violence exposure, few studies have examined the importance of social context. The present study examined classifications of youth exposed to violence by contextual location (home, school, and neighborhood) in a sample of 2,124 juvenile justice involved youth. Latent class analysis revealed three classes of youth exposed to violence: (a) low violence exposure, (b) moderate and high home/school violence exposure, and (c) violence exposure in all three social contexts. Furthermore, distal outcomes analysis showed differences in internalizing and externalizing problems based on class membership. Findings from the current study underline the importance of understanding the role of social context in assessing violence exposure in juvenile justice involved youth.